PENGARUH KEBIJAKAN MAKROPRUDENSIAL TERHADAP RESIKO KREDIT MACET PADA BPR KONVENSIONAL DI INDONESIA - Tesa Uci Yugita; Ali Anis; Alpon Satrianto (Universitas Negeri Padang, 2017)
This research purpose are to the analyse the (1) LTV Policy, (2)Interest rates on Consumption Loans (3) The Capital Adequacy Ratio in terms of the Non Performing Loans in BPR convensional Indonesia. Methods that being used are Ordinary Least Square (OLS), the estimation results show that (1)LTV Policiy has a significant positive effect the Non Performing Loans in BPR convensional Indonesia (2) Interest rates on consumption loans has a significant positive effect on Non Performing Loans in BPR convensional Indonesia, and(3) The Capital Adequacy Ratio has a significant positiveeffects the Non Performing Loan in BPR convensional Indonesia.